FORMULATION AND EVALUATION OF ALGINATE-BASED MUCOADHESIVE BUCCAL PATCH FOR DELIVERY OF ANTIMIGRAINE DRUG - Asthana, Gyati Shilakari; Sharma, Sumit; Asthana, Abhay (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present work was aimed with enhancement of oral bioavailability of sumatriptan succinate by sodium alginate-based mucoadhesive buccal patches. Methods: These patches were prepared by solvent-casting method using different concentrations of sodium alginate along with HPMC 5cps and maltodextrin as a film-forming polymer. Propylene glycol, sodium lauryl sulfate, and mannitol were used as plasticizer, penetration enhancer, and filler, respectively. Prepared patches were evaluated with respect to various in vitro parameters and in vivo studies were conducted on white strain New Zealand rabbits of either sex with average weight 2â€“3 kg. Results: All the formulations were transparent and homogeneous. F7 formulation containing Na alginate (250 mg), maltodextrin (250 mg), and HPMC 5cps (250 mg) displayed maximum folding endurance, mucoadhesive force, in vitro drug transport, and drug release and found to be stable up to 2 months in storage conditions. The pharmacokinetic parameters such as Cmax, tmax, and AUC were calculated from the data collected after in vivo studies. Sumatriptan succinate containing buccal patch displayed almost 1.73 folds and 2 folds higher Cmax and AUC, respectively, than plain drug solution. 1.93% of relative bioavailability was reported with the formulation. Conclusion: The outcome of the present work reveals that sumatriptan succinate-based mucoadhesive buccal formulation can improve overall performance of drug molecule in vitro and in vivo.